The Influence of Motivation Strategy, Rewards, Training and Career Development on Employee Retention Through Job Satisfaction as an Intervening Variable at PT. Manggalakarya Bangun Sarana - Javan Agustian Setyagraha; Supardi Supardi; Vera Firdaus (Green Publisher Indonesia, 2025)
This research aims to examine the influence of motivation strategies, rewards, training, and career development on employee retention, with job satisfaction as an intervening variable at PT. Manggalakarya Bangun Sarana. The main issue addressed in this research is the low level of employee retention, which can negatively impact the company’s operational continuity and efficiency. Therefore, understanding the internal factors that influence employees’ decisions to remain with the company is essential. This research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 150 permanent employees selected using purposive sampling, focusing on individuals with a minimum of one year of service. The collected data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) and processed with SmartPLS software. The results of the analysis show that all four independent variables—motivation, rewards, training, and career development—have a positive and significant influence on job satisfaction, both simultaneously and partially. Job satisfaction itself is proven to have a positive and significant effect on employee retention. Furthermore, job satisfaction significantly mediates the relationship between motivation, rewards, training, and career development with employee retention. These findings suggest that, to improve employee retention, the company must focus on strategies that enhance job satisfaction, such as effective motivation programs, fair reward systems, relevant training, and well-structured career development opportunities. Consequently, the implementation of effective human resource strategies can directly impact increased employee loyalty and long-term commitment to the company.